The Influence of Environmental Awareness and Work Discipline on Waste Management Effectiveness among Hotel Employees - Laraswati; Wahyu Ari Indriastuti (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose : This study aims to analyze the influence of environmental awareness and employee work discipline on the effectiveness of waste management in the hospitality industry. Method : This quantitative study was conducted at Anaya Azana Boutique Hotel Tawangmangu, targeting a population of all staff members involved in waste management. Primary data were collected through the distribution of questionnaires using a 1–5 Likert scale to 30 respondents selected via a saturation sampling technique (census). Secondary data were utilized as contextual support to reinforce the background of the study and provide an overview of the research object. Data analysis was performed using SPSS software, encompassing instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. Result: This study shows that both variables have a positive and significant effect on waste management effectiveness. Work discipline demonstrated a stronger relative effect (β= 0.749, B = 0.702, t = 8.859, p < 0.001), indicating that higher employee compliance with Standard Operating Procedures (SOP) substantially enhances waste management practices. Environmental awareness also exerted a statistically significant positive effect (β = 0.254, B = 0.257, t = 3.002, p = 0.006), confirming that greater environmental concern improves waste management quality. Simultaneously, both variables were proven to be statistically significant (F = 200.709, p < 0.001), with the research model explaining 93.2% of the variance in waste management effectiveness (Adjusted R2 = 0.932) Contribution: This study provides empirical evidence that both environmental awareness and employee work discipline particularly in adhering to SOP play a crucial role in supporting successful and sustainable waste management within the hospitality industry.